Genetic Modification Strategies to Enhance CAR T Cell Persistence for Patients With Solid Tumors - DeRenzo, Christopher; Gottschalk, Stephen (Frontiers in Immunology, 2019)
Immunotherapy with chimeric antigen receptor (CAR) T cells offers a promising method to improve cure rates and decrease morbidities for patients with cancer. In this regard, CD19-specific CAR T cell therapies have achieved dramatic objective responses for a high percent of patients with CD19-positive leukemia or lymphoma. Most patients with solid tumors however, have experienced transient or no benefit from CAR T cell therapies. Novel strategies are therefore needed to improve CAR T cell function for patients with solid tumors. One obstacle for the field is limited CAR T cell persistence after infusion into patients. In this review we highlight genetic engineering strategies to improve CAR T cell persistence for enhancing antitumor activity for patients with solid tumors.